Seeking the 'Centre of the Tornado': Ursula Fleming, Meister Eckhart and Pain. Issue 2 (3rd July 2019) - Stephens, Rebecca
ABSTRACT: The Eckhart Society was founded by Ursula Fleming, who worked in the field of pain control. She had found that a doctrine of acceptance and self-grounding, through focus on breath and letting-go, enabled even those suffering insupportable pain to reduce their suffering. Her simple and practical approach was profoundly influenced by her study of Meister Eckhart, whose rehabilitation she advocated. This paper explores the connections between them, and how an Eckhartian understanding can assist us in living through pain and fear.